Profitability, Liquidity, and Costs as Determinants of Corporate Tax Expenses: Profitabilitas, Likuiditas, dan Biaya sebagai Penentu Beban Pajak Perusahaan - Hidayati, Nurul Dwi; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Corporate income tax impacts financial performance, particularly in regulated sectors like food and beverage manufacturing. Gap: Limited studies analyze how profitability, liquidity, leverage, and operating costs affect tax expenses in emerging markets. Aims: This study examines these financial factors’ effects on corporate income tax for food and beverage firms listed on the IDX from 2017-2021. Results: Quantitative analysis shows profitability and leverage significantly influence tax expenses, while liquidity does not; operating costs are also impactful. Novelty: This study underscores profitability and leverage as key tax determinants in Indonesia’s food and beverage sector. Implications: Findings guide financial planning and policy, helping optimize tax outcomes in similar emerging markets. Highlights : Profitability and leverage significantly impact corporate tax expenses. Liquidity shows no significant effect on income tax expenses. Findings aid in optimizing tax strategies for manufacturing sectors. Keywords: Profitability, Liquidity, Leverage, Operating Costs, Income Tax